An analysis of the Turkish agricultural sector: long-term sustainability question in the post-2000 era - Köymen, Gülcan Melis (İstanbul Bilgi Üniversitesi, 2020)
ABSTRACT: The Agricultural production that had been under strict control in the state in Turkey until 1980, has passed through a gradual structural transformation which was completed with the twin reform package that was enforced by the International Monetary Fund (IMF) and the World Bank (WB) in the early 2000s. The reform package propelled by the IMF and WB contained a series of policies in the name of streamlining the economy in accordance with the free-market conditions and pointed out the ‘state’ as the scapegoat of malfunctioning agriculture. Thus, the role of the state and its parastatal institutions in agricultural production were abolished vigorously during the following decade while the subsidies that had been used to sustain the welfare of rural masses were minimized at the expense of creating impoverishment and unemployment. Obviously, the alteration towards exportoriented liberal policies accompanied by the haphazardly taken governmental decisions to maintain legitimacy in 1990s, drifted Turkey into successive economic crises and ultimately compelled the country to sign the IMF/WB loan agreements, in exchange for losing its sovereignty in strategy-making decisions within major sectors including agriculture. However, in order to provide a complete understanding on the nature of agrarian transformation in Turkey the international capitalization process of agriculture, on behalf of US-dominated transnational companies (TNCs), needs to be evaluated. Moreover, the requirements of the European Union (EU) alignment and the pledges that were given to the WTO (World Trade Organization) in the Doha Round talks needs to be examined. This thesis aims to present an analysis on the post-2000 agricultural transformation and capitalization in Turkey that was imposed via neoliberal reforms and international agreements. It contends that the present agricultural support policies of Turkey are far from being either protectionist or viable in real terms and incapable of providing long-term sustainability in terms of national food-security, rural development and economic improvement concerning the multilateral dependencies of the country.

ÖZET: Türkiye’de 1980 yılına kadar devletin sıkı kontrolüne tabi olan tarımsal üretim takip eden yıllarda kademeli olarak yapısal bir dönüşüm geçirmiş, liberalleşme yönünde gerçekleşen bu dönüşüm 2000’li yılların başında Uluslararası Para Fonu (IMF) ve Dünya Bankası (WB) tarafından dayatılan ikiz reform paketi ile tamamlanmıştır. IMF ve DB menşeili reform paketi ekonomiyi daha verimli hale getirme iddiasıyla Türkiye’yi serbest piyasa koşullarına uyumlandırma yolunda bir dizi tedbir içermekte, devleti ise diğer alanlarda olduğu gibi tarımda da aksaklıkların birincil sorumlusu ilan etmekteydi. Takip eden on yıl içinde süregelen destekleme politikaları, kırsal alanda fakirleşme ve işsizlik pahasına, asgari seviyelere indirilmiş, devlet ve kamusal kuruluşlar tarım üretimi alanında beklenmedik bir hızla hükümsüz kılınmıştır. İhracat odaklı liberal politikalar yönünde gerçekleşen eksen kayması, 1990’larda hükümetlerin kendi meşruiyetlerini korumak namına aldıkları gelişigüzel kararlarla bir araya gelince Türkiye’nin art arda gelen ekonomik krizlere sürüklendiği ve nihai olarak ülkenin kendi lokomotif sektörlerinde strateji geliştirme özerkliğini kaybetmek pahasına bahsi geçen IMF/DB kredi sözleşmelerini imzalamaya mecbur kaldığı açıkça görülmektedir. Bununla birlikte, tarımsal dönüşümün doğasını tam anlamıyla kavrayabilmek için -ağırlıklı Amerika bazlı- ulus-ötesi şirketler yararına gerçekleşen küresel sermayelendirme sürecinin değerlendirilmesi gerekmektedir. Ayrıca, Avrupa Birliği (EU) uyum koşulları ile Uruguay ve Doha müzakereleri kapsamında Dünya Ticaret Örgütü’ne (DTÖ) verilmiş olan taahhütler önem arz etmektedir. Bu tez, 2000’li yılların başından itibaren, Türkiye’de tarım alanında yapısal bir dönüşüme sebep olan neoliberal reformları ve uluslararası anlaşmaların bağlayıcı niteliklerini inceleyerek, yerini küresel sermayeye bırakmak suretiyle geri çekilen devletin, korumacı politikalarına dair bir inceleme sunmayı hedeflemektedir. Mevcut destekleme politikalarının, ülkenin çok taraflı tabiiyetleri göz önünde bulundurulduğunda, ulusal gıda güvenliği, kırsal gelişme ve ekonomik ilerleme bağlamında uzun vadeli sürdürülebilirlik sağlamaktan ve gerçek anlamda korumacılıktan ve tutarlılıktan uzak olduklarını ileri sürmektedir.
Türkiye’de tarım sektörü üzerine bir inceleme: 2000 yılı sonrası dönemde uzun vadeli sürdürülebilirlik sorunsalı
Keywords: Tarımsal Destekleme Politikaları; Korumacılık; Neoliberal Reformlar; Tarımsal Sürdürülebilirlik; Tarım Ekonomi Politiği; Agricultural Support Policies; Protectionism; Neoliberal Reforms; Sustainability in Agriculture; Economy Politics of Agriculture